1992
DOI: 10.1063/1.350443
|View full text |Cite
|
Sign up to set email alerts
|

Atomic force microscopy of (100), (110), and (111) homoepitaxial diamond films

Abstract: We present atomic force microscopy images of diamond films grown by chemical vapor deposition epitaxially on diamond (100), (110), and (111) substrates. The films were grown from 0.2%–1.6% mixtures of CH4 and C2H2 in H2 in a hot-filament reactor at a total pressure of 25 Torr. The substrate and filament temperatures were held at 810–1000 and 2000–2150 °C, respectively. A (100)-oriented diamond film grown with 0.3% CH4 at a substrate temperature of 810 °C was rough on the μm scale, exhibiting pyramidal features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(21 citation statements)
references
References 82 publications
0
21
0
Order By: Relevance
“…For example, because of the alternating nature of the dimer/trough mechanism, we found that neighboring dimer rows cannot grow until the trough between them has been spanned. However this approach does not account for the relatively smooth surfaces that have sometimes been observed over long ranges on the (100)-(2 x 1):H surface [28,30,31]. On metals and some other types of crystals, smooth surfaces are the result of loosely bound adatoms diffusing to steps and kinks, which lowers their energy (by increasing their coordination numbers) and leads preferentially to growth at those sites.…”
Section: Atomically Smooth Surfaces On Diamondmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, because of the alternating nature of the dimer/trough mechanism, we found that neighboring dimer rows cannot grow until the trough between them has been spanned. However this approach does not account for the relatively smooth surfaces that have sometimes been observed over long ranges on the (100)-(2 x 1):H surface [28,30,31]. On metals and some other types of crystals, smooth surfaces are the result of loosely bound adatoms diffusing to steps and kinks, which lowers their energy (by increasing their coordination numbers) and leads preferentially to growth at those sites.…”
Section: Atomically Smooth Surfaces On Diamondmentioning
confidence: 99%
“…Howuver, it is unlikely that such a surface would be stable because of very large H -H steric repulsions [26]. Recent STM and AFM experiments have shown [27][28][29] that diamond surfaces can be rather rough on an atomic scale, but at least some of the surface reconstructs to the (100)-(2x1):H form [28,30,31]. On this surface each carbon atom is bonded twice to carbons in the bulk, once to a surface hydrogen, and once to a neighboring surface carbon making a "dimer" and forming a 5-membered ring, as seen in Figure 2.…”
Section: Introductionmentioning
confidence: 99%
“…This surface has been observed experimentally [25,26] postulates that once a CH 3 radical adds to the diamond surface, it has a choice: it can either desorb thermally or it can undergo further reactions with gas phase H 11 atoms that lead to incorpuration of its carbon into the lattice. Since the desorption and incorporation rates can be on the same order of magnitude, the growth rate depends sensitively on the branching ratio into these two pithways.…”
Section: Growth Rate Modelingmentioning
confidence: 99%
“…On the right hand side of the vertical line, the formation energy of CH 4 is negative, namely, CH 4 forms spontaneously from the C(100) surfaces in the presence of the hydrogen reservoir. In contrast, the left side of the vertical line has a positive formation energy for CH 4 . The most stable surface phases for this region are: the bare surface when H is smaller than 17.19 eV, the Fig.…”
Section: B Energeticsmentioning
confidence: 99%
“…Since the hydrogen is always bonded to a single C atom, so it is reasonable to assume a zero-point energy proportional to the number of H atoms: 27 E 0 = n H e 0 . We estimated e 0 by the sum of vibrational frequencies of a typical hydrocarbon CH 4 and set it to 0.293 eV (0.0215 Ry) per hydrogen. 36 Temperature dependence of the formation energy was mainly incorporated through the chemical potential of hydrogen.…”
Section: B Energeticsmentioning
confidence: 99%